Variations on the body - Serres, Michel (Univocal, 2011)
World-renowned philosopher, Michel Serres writes a text in praise of the body and movement, in praise of teachers of physical education, coaches, mountain guides, athletes, dancers, mimes, clowns, artisans, and artists. This work describes the variations, the admirable metamorphoses that the body can accomplish. While animals lack such a variety of gestures, postures, and movements, the fluidity of the human body mimics the leisure of living beings and things; what's more, it creates signs. Already here, within its movements and metamorphoses, the mind is born. The five senses are not the only.